Experiences of older people following an acute exacerbation of chronic obstructive pulmonary disease: A phenomenological study. Issue 5 (21st February 2018) - Rosa, Francesca; Bagnasco, Annamaria; Ghirotto, Luca; Rocco, Gennaro; Catania, Gianluca; Aleo, Giuseppe; Zanini, Milko; Dasso, Nicoletta; Hayter, Mark; Sasso, Loredana
Abstract : Aims and objectives: To explore the experience of patients affected by chronic obstructive pulmonary disease following hospitalisation due to an acute exacerbation event. Background: Chronic obstructive pulmonary disease is a progressively debilitating disease, often with very burdensome symptoms such as acute and chronic breathlessness and fatigue. Acute exacerbation often creates a life‐threatening event. Exacerbation can also have substantial psychological effects including anxiety and depression although this aspect is less well researched—especially amongst people with chronic obstructive pulmonary disease recovering from an acute event and facing a return home. Design: A descriptive phenomenological study. Methods: In‐depth interviews were conducted with 12 chronic obstructive pulmonary disease patients recently recovering from an acute exacerbation of their chronic obstructive pulmonary disease. Data were analysed using Colaizzi's phenomenological framework. Results: Four themes were identified from the data: a sense of loss and frustration, hopelessness, uncertainty about the future and fear of becoming a burden. Participants expressed quite negative views including a loss of hope, uncertainty about their future care and the burden they may become on their families. They appeared stressed and anxious as a result of the acute event they had experienced. Conclusions: This study shows that an acute episode of illness can generate a sense of hopelessness and uncertainty about their future care in people with chronic obstructive pulmonary disease. This occurs as they recover physically and think about the future, often in quite negative terms. Relevance to clinical practice: For healthcare professionals, it is important to take into account the potential feelings of loss, hopelessness and uncertainty that people can experience following an acute exacerbation of their chronic obstructive pulmonary disease and ensure that psychological care is available as physical recovery takes place. Such care to include good discharge planning, giving patients time to express concerns and referral to counselling services if appropriate.